C6-Substituted methanopyrrolidine β-amino acid: synthesis and characterization of oligomeric foldamers. Issue 35 (27th August 2020) - Hu, Zilun; Lin, Guoliang; Sender, Matthew; Cannon, Kevin C.; Davis, Franklin A.; Krow, Grant R.
Graphical abstract: Highlights: Highly conformation constrained β-proline based methanopyrrolidine-5-carboxylic acids are synthesized. C6-Substitution effects subtly the cis/trans- amide conformation. Circular dichroism characterization of the oligomers indicates order of folding. Enhanced order of folding uniformity is demonstrated at higher oligomer level. Abstract: Highly conformation constrained β-proline based methanopyrrolidine-5-carboxylic acids (6, MetPyr-5-acids, or MetPyr-β-amino acids) derivatives were designed, synthesized, and investigated to control peptide conformation and oligomer folding. Enhanced order of folding uniformity correlated with length of the prepared homo -oligomers as characterized by circular dichroism (CD). The octamer (34 ) exhibited minimal solvent effects and was stable with increasing temperature up to 80 °C. Substitutions on C 6 of the 2-azabicyclo[2.1.1] hexane structure could modulate the amide cis/trans conformation.